Central Projections of Antennal and Labial Palp Sensory Neurons in the Migratory Armyworm Mythimna separata - Ma, Bai-Wei; Zhao, Xin-Cheng; Berg, Bente G.; Xie, Gui-Ying; Tang, Qing-Bo; Wang, Gui-Rong (Frontiers in Cellular Neuroscience, 2017)
The oriental armyworm, Mythimna separata (Walker), is a polyphagous, migratory pest relying on olfactory cues to find mates, locate nectar, and guide long-distance flight behavior. In the present study, a combination of neuroanatomical techniques were utilized on this species, including backfills, confocal microscopy, and three-dimensional reconstructions, to trace the central projections of sensory neurons from the antenna and the labial pit organ, respectively. As previously shown, the axons of the labial sensory neurons project via the ipsilateral labial nerve and terminate in three main areas of the central nervous system: 1) the labial-palp pit organ glomerulus of each antennal lobe, 2) the gnathal ganglion, and 3) the prothoracic ganglion of the ventral nerve cord. Similarly, the antennal sensory axons project to multiple areas of the central nervous system. The ipsilateral antennal nerve targets mainly the antennal lobe, the antennal mechanosensory and motor center, and the prothoracic and mesothoracic ganglia. Specific staining experiments including dye application to each of the three antennal segments indicate that the antennal lobe receives input from flagellar olfactory neurons exclusively, while the antennal mechanosensory and motor center is innervated by mechanosensory neurons from the whole antenna, comprising the flagellum, pedicle, and scape. The terminals in the mechanosensory and motor center are organized in segregated zones relating to the origin of neurons. The flagellar mechanosensory axons target anterior zones, while the pedicular and scapal axons terminate in posterior zones. In the ventral nerve cord, the processes from the antennal sensory neurons terminate in the motor area of the thoracic ganglia, suggesting a close connection with motor neurons. Taken together, the numerous neuropils innervated by axons both from the antenna and labial palp indicate the multiple roles these sensory organs serve in insect behavior.